Conditional prescriptions of oral antihypertensive drugs for the management of hypertension urgencies in the inpatient setting: An observational study. (28th September 2019) - Pieragostini, Rémi; Perrin, Germain; Nevoret, Camille; Amar, Laurence; Jannot, Anne‐Sophie; Sabatier, Pierre; Korb‐Savoldelli, Virginie; Sabatier, Brigitte
Abstract: What is known and objectives: The management of hypertension urgencies during hospitalization may generally not necessitate urgent care. However, physicians frequently prescribe 'as needed' antihypertensive drugs for which administration is triggered by blood pressure thresholds. The lack of rationale for this hospital practice led us to study oral conditional antihypertensive (OCA) prescriptions. We aimed to estimate the prevalence of OCA prescriptions and to establish their characteristics. Methods: In our institution, prescriptions are computerized. The study was retrospectively performed using a hospital clinical data warehouse over a 5‐year period. Results and discussion: The prevalence of OCA prescriptions was 6.9% among subjects treated with an antihypertensive drug. The median duration of these prescriptions was 4 days, until the day of the patient discharge in 78.8% stays. The calcium channel inhibitors were the main (79.9%) pharmacological class prescribed, with mostly prescriptions of nicardipine. OCA prescriptions were associated with another antihypertensive medication in 58.8% of the prescriptions; for 19.3%, it was a medication belonging to the same pharmacological class than the OCA drug prescribed. Regarding the computerized drafting, 39.6% of the conditional prescriptions were considered uninterpretable. At least one administration by nurses concerned 65.1% of the OCA prescriptions. The mean SBP and DBP before the initiation of an OCA drug was 142.9 ± 28.2 and 75.8 ± 24.5 mm Hg, respectively, relative to 143.0 ± 24.9 and 77.6 ± 19.9 mm Hg after the initiation ( P  = .8 for SBP and P  = .06 for DBP). What is new and conclusion: The originality of this study lies in the use of a clinical data warehouse to evaluate OCA prescriptions in hospital. These prescriptions are current, often uninterpretable and mostly ordered until patient discharge. Such drug orders could be associated with an increased risk of iatrogenic events and/or administration errors. This underlies the need for developing decision support tools and computerized protocols to manage hypertension urgencies. Abstract : Despite a lack of recommendations, prescriptions of oral conditional antihypertensive drugs are current. Using a clinical data warehouse allowed us to highlight that such prescriptions were often not clearly drafted and may lead to administration errors.